TERRITORIALIZAÇÃO E DESENVOLVIMENTO LOCAL: UM ESTUDO DAS FAZENDAS CAFEEIRAS DE MUQUI/ES - Bernardo, Luciano Correia (2020)
This research is developed within the scope of applied social sciences, and proposes to establish a dialogue between territorialization and self-sustainable development in order to return places to the project through an investigative process about th